(untitled) (Homiletic, 2012)
In the mid 1220s Anthony of Padua, who had lectured on Sacred Scripture for a year at a Franciscan School that he had established in Bologna, was asked to write out his lectures. Instead he wrote a resource book for preachers. This contained material for all Sundays of the year and its major feast days, a more practical treatise for fledging preachers because it also contained pointers on how to preach. Among the resources are comparisons between characteristics of animals, plants, and minerals with human characteristics. This paper investigates what influenced Anthony, analyzes his probable resources, and lists all the creatures from his general animal “zoo” together with examples of his contrasting of animal and humans characteristics.